Morphometric and Phylogeneticanalysis of Pipistrellus Kuhlii Captured from Fata Regions, Pakistan - Iftikhar Hussain, Asif Ali, Shujaat Hussain, Amir Hussain, Javed Ahmed Ujjan, Fahim Haider Jamali, Khalid Usman, Muhammad Shahbaz, Nadia Saeed, Qasim Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The present study was carried out to explore the distribution of Pipistrellus kuhlii in selected area of FATA regions, Pakistan. Findings & Practical implication: Twenty six specimens of this species were collected using mist from Bara Khyber agency (33º 92 N; 71.46º E) and Tirah Aurakzai agency (33º 78 N; 70.70º E) in FATA. Mean body mass of Pipistrellus kuhlii was recorded 8.42g ± 2.14. Head and body length were observed 44.2 ± 3.5 respectively. Ear length was recorded 12.2 ± 0.8. For molecular analysis the sequences of CO1 gene were obtained and analyzed. The mean intraspecific divergences of Pipistrellus kuhlii was 0.093%. The interspecific average distance between Pipistrellus kuhlii and P. tennius were 12.48% and distance between Pipistrellus kuhlii and P. javanicus were 18.6%. Nucleotide mean concentration was A = (24.9%), T = (32.2%), G = (18.2%) and C = (24.7%). The mean A+T contents were 57.1%and C+G were 42.9%. Conclusion: From the current research studied it may be concluded that the measurements of body matching with the specimens reported from Sri Lanka, Pakistan, Nepal and India. In the phylogenetic tree Pipistrellus kuhlii and P. nanulus clustered with significant bootstrap support value. Keywords: Pipistrellus kuhlii, Morphology, Kurram Agency, Bats, Pakistan